Role of Learners’ Interests and Talents in Their Choice of Senior Secondary School Pathways in Bumula Sub County, Bungoma County, Kenya (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The implementation of the Competency-Based Education (CBE) curriculum in Kenya emphasizes pathway selection based on learners' interests, talents, strengths, and career aspirations. However, limited empirical evidence exists on the extent to which learners' interests and talents influence their choice of senior secondary school pathways, particularly in rural contexts. This study examined the role of learners' interests and talents in the choice of senior secondary school pathways among Grade Nine learners in Bumula Sub-County, Bungoma County, Kenya. The study adopted a mixed methods research design. The target population comprised approximately 3,500 Grade Nine learners in public junior secondary schools, together with career guidance teachers, school heads, and selected parents. Using the Krejcie and Morgan sampling table, a sample of 347 learners was selected through stratified random sampling from twenty public junior secondary schools. Quantitative data were collected using questionnaires, while qualitative data were obtained through interviews. Quantitative data were analysed using descriptive statistics, including frequencies, percentages, means, and standard deviations, while qualitative data were analysed thematically. The findings revealed that learners' interests and talents significantly influenced pathway selection. Most respondents indicated that their personal interests influenced their pathway choices (M = 3.98), their talents matched their selected pathways (M = 3.87), they enjoyed subjects related to their preferred pathways (M = 4.01), and they were passionate about their chosen pathways (M = 3.93). Conversely, most learners disagreed that they selected pathways that did not match their interests (M = 2.39). The study concludes that learners generally choose pathways that align with their interests, talents, and aspirations, although a minority continue to be influenced by external factors such as parental expectations, school limitations, and inadequate career guidance. The study recommends that schools strengthen career guidance programmes and create opportunities to identify and nurture learners' interests and talents through co-curricular activities, mentorship, and practical learning experiences to promote informed and learner-centred pathway selection.